2021
DOI: 10.1038/s41598-021-90788-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between moderated level of air pollution and fetal growth: the potential role of noise exposure

Abstract: This study aims to analyze, in a population of singletons, the potential confounding or modifying effect of noise on the relationship between fetal growth restriction (FGR) or small for gestational age (SGA) and environmental exposure to air pollution. All women with single pregnancies living in one of two medium-sized cities (Besançon, Dijon) and who delivered at a university hospital between 2005 and 2009 were included. FGR and SGA were obtained from medical records. Outdoor residential exposure to nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Exposure to environmental noise from factories, trains, and airplanes before conception and during pregnancy has been associated with delayed time to achieve pregnancy 33 . Numerous studies have investigated how noise affects both fetal growth and embryogenic size; however, some studies have shown effects of noise on growth, whereas others have not shown any effects 6–12 . Currently, the effects, if any, on noise exposure and embryonic/fetal growth remain uncertain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to environmental noise from factories, trains, and airplanes before conception and during pregnancy has been associated with delayed time to achieve pregnancy 33 . Numerous studies have investigated how noise affects both fetal growth and embryogenic size; however, some studies have shown effects of noise on growth, whereas others have not shown any effects 6–12 . Currently, the effects, if any, on noise exposure and embryonic/fetal growth remain uncertain.…”
Section: Methodsmentioning
confidence: 99%
“…33 Numerous studies have investigated how noise affects both fetal growth and embryogenic size; however, some studies have shown effects of noise on growth, whereas others have not shown any effects. [6][7][8][9][10][11][12] Currently, the effects, if any, on noise exposure and embryonic/fetal growth remain uncertain.…”
Section: Effect(s) Of Noise On Embryonic/fetal Growthmentioning
confidence: 99%
“…Also, their harmful effect on birth outcomes have been displayed in several studies [ 2 , 10 , 11 , 12 ], and it has been estimated that about 100,000 of deaths per year worldwide could be linked to this exposure [ 9 ]. Recent meta-analyses have highlighted the significant association between air pollution due to traffic and LBW [ 13 , 14 , 15 ] and more studies have shown how adverse birth effects were linked to maternal residential proximity to a mayor traffic density area, to heavy traffic lights, to bus stations, and to several ring and major roads [ 9 , 16 , 17 , 18 , 19 , 20 ]. To support this evidence, it has been shown that air pollution can lead to an increase in cell proliferation, organ development changes and modification on fetal metabolism, that can cause especial vulnerability and damage during the states of pregnancy and the neonatal period [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%